npregfast: An R Package for Nonparametric Estimation and Inference in Life Sciences - Sestelo, Marta; Villanueva, Nora M.; Meira-Machado, Luis; Roca-Pardiñas, Javier (Journal of Statistical Software, 2017)
We present the R npregfast package via some applications involved with the study of living organisms. The package implements nonparametric estimation procedures in regression models with or without factor-by-curve interactions. The main feature of the package is its ability to perform inference regarding these models. Namely, the implementation of different procedures to test features of the estimated regression curves: on the one hand, the comparisons between curves which may vary across groups defined by levels of a categorical variable or factor; on the other hand, the comparisons of some critical points of the curve (e.g., maxima, minima or inflection points), studying for this purpose the derivatives of the curve.